The Effect of Mental Toughness on Learning Burnout of Junior Middle School Students: Putting School Adaptation as a Mediator Variable - Qi Fengjun; Zhou Jing; Li Liguang (Discrete Dynamics in Nature and Society)
Learning burnout has always been a key problem in school education. Junior high school students, as an important part of the student population, cannot be ignored. To explore the impact of resilience, school adaptation on learning burnout is helpful to improve students’ learning level and reduce learning burnout. In this study, the junior high school students in A city were selected as the research objects, and questionnaires were used to explore the effect of mental toughness on learning burnout and the mediating effect of school adaptation. Statistical analysis methods such as descriptive statistics, correlation analysis, and regression were used. Based on the theoretical model of job burnout, data analysis showed that mental toughness of junior high school students in A city could significantly negatively predict learning burnout. Adolescent mental toughness can significantly affect the prediction of school adjustment school adjustment has a significant negative impact on learning burnout, and mental toughness can indirectly affect learning burnout through school adjustment.